Penggunaan Media Kartu Angka untuk Meningkatkan Kemampuan Pemahaman Bilangan 1-20 Pada Anak ADHD - Nabila, Putri Zidni; Maharani, Choirunisa Putri; Ruby, Arcivid Chorynia (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to evaluate the extent to which number card media can help improve children's ability to understand numbers 1–20, especially for children with Attention Deficit Hyperactivity Disorder (ADHD). The study was conducted at the Child Welfare Institution (LKSA) with a descriptive qualitative approach. The subject of this study was a child with ADHD who had difficulty recognizing and understanding numbers. Data were collected through observation, interviews, and documentation. Data analysis was carried out using a qualitative descriptive method using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The findings of this study indicate that consistent use of number card media can improve children's concentration, enthusiasm for learning, and ability to recognize and pronounce numbers 1–20. The learning process is also supported by the Picture and Picture method and LKPD which are adjusted to children's interests, such as coloring. Number card media functions as a visual tool and educational game, providing an interesting and meaningful learning experience for children with ADHD. This study recommends the application of concrete learning media as an alternative teaching strategy for children with special needs.